Bacterial community shifts associated with high abundance of Rhizobium spp. in potato roots under macronutrient-deficient conditions. (January 2015) - Unno, Yusuke; Shinano, Takuro; Minamisawa, Kiwamu; Ikeda, Seishi
Abstract: We evaluated the impacts of a macronutrient deficiency on the community structure of root-associated bacteria in potato ( Solanum tuberosum ) cultivation. Potato plants were cultivated in a long-term experimental field under a nitrogen, phosphorus, or potassium deficiency, and roots were sampled at the early flowering stage. Amplicon libraries of 16S rRNA gene were constructed for root-associated bacteria, and bacterial diversity was analyzed by means of pyrosequencing. Statistical analyses showed significantly lower species evenness in the nutrient-deficient plots compared with the value in a plot with standard fertilization. Phylogenetic analyses revealed that the abundance of Rhizobium spp. increased dramatically in all plots under a macronutrient deficiency. Highlights: Diversity of potato root-associated bacteria in nutrient deficiency was examined. Root-associated bacteria in nutrient deficiency showed low evenness. Abundance of Rhizobium sp. was dramatically increased in nutrient deficiency.